Hybrid polymer composite materials : structure and chemistry - Thakur, Vijay Kumar; Thakur, Manju Kumari; Gupta, Raju Kumar, 1982- (Woodhead Publishing series in composites science and engineering., 2017)
This book presents the latest on these composite materials that can best be described as materials that are comprised of synthetic polymers and biological/inorganic/organic derived constituents.